A STUDY ON PHYTOCHEMICALS, ANTIMICROBIAL, AND SYNERGISTIC ANTIMICROBIAL ACTIVITIES OF HIBISCUS SABDARIFFA - SIVAN KUMAR; ANNA SHEBA L (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The aim of the present study was to screen phytochemical constituents and evaluate antimicrobial and synergistic antimicrobial properties of leaves and stem of Hibiscus sabdariffa. Methods: The extraction was done by cold maceration method using 80% aqueous methanol. The antimicrobial efficacy and synergistic antimicrobial activity were carried out by disc diffusion assay against the bacteria Staphylococcus aureus and Pseudomonas aeruginosa. Results: Phytochemical analysis revealed the presence of carbohydrate, protein, alkaloids, phytosterols, flavonoids, and diterpenes in both the leaves and stem extracts while saponins, phenol, and tannins were found to be present only in the leaf extract. Both the extracts inhibited the tested bacteria with minimum inhibitory concentration value of 10 mg/ml. Aqueous methanolic extract of leaf showed higher antibacterial activity against S. aureus and P. aeruginosa and also exhibited synergistic activity with the antibiotic chloramphenicol against S. aureus. Conclusion: The present study concludes that H. sabdariffa is a potential source of bioactive components and also provides information on synergistic activity of leaf extract. The results can contribute to the development of potent antibacterial agents.